Masih Tentang Persoalan Metodologis Ilmu Pemerintahan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRAK This article written with basic assumptions that study on government is a part of political science, in a line with interesting de Ve. r enr of the last two decades concerning the diversification of output.from various institution deals with study on government- Beside, development of the study on government also becomes more complex and varied. The concept of power that is basically the main locus of the study is 7014) relative: it now defined as actors whose larger influence than other actors in wrtain social context. That is, power is attributed to some actors with a different basis such as culture, economy., social class, degree of education, etc. Somebody may have multi-basis so then he he may influence other people in various socia/ sphere. Consequently, every activity can easily considered as a political phenomenon. But the expansion of the subject is not equal with its theoretical, concept and methodological development in order to comprehend contemporaries_ The subject developed with geometrical line, but the scientist's capability to understand it developed through arithmetical line, There are too many politiccd phenomenons which are ignored in the "situation of anomaly'. Political scientist does not have sufficient instruments to answer this anomaly. Or vice versa, political scientist has become a servant of methodological development (especially quantitative method) so they tend to produce reality than to inductively conceptuali2e neul